2022
DOI: 10.1001/jamaoncol.2022.4327
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cutaneous Adverse Events With Phosphoinositide 3-Kinase Inhibitors as Adjuvant Therapy in Patients With Cancer

Abstract: ImportanceThe phosphoinositide 3-kinase (PI3K) pathway is among the most frequently activated pathways in human cancers. As the use of PI3K inhibitors for cancer treatment grows, there is increasing need for understanding the cutaneous effects associated with these therapies.ObjectiveTo systematically review the published literature reporting incidence of cutaneous adverse events with PI3K inhibitors and to provide pooled incidence estimates using meta-analysis.Data SourcesThis systematic review and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 47 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…In addition, we originally reported that subgroup analyses found an inconclusively higher incidence of severe rashes with the use of Pan-class compared with isoform-selective PI3K inhibitors; corrected subgroup analyses revealed that the incidence of severe rashes did not differ significantly between classes of PI3K inhibitors. These corrections do not change the overall results and conclusions of our study, 1 which continues to find an increased risk of all-grade and severe-grade (3-5) eruptions associated with PI3K inhibitors.…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…In addition, we originally reported that subgroup analyses found an inconclusively higher incidence of severe rashes with the use of Pan-class compared with isoform-selective PI3K inhibitors; corrected subgroup analyses revealed that the incidence of severe rashes did not differ significantly between classes of PI3K inhibitors. These corrections do not change the overall results and conclusions of our study, 1 which continues to find an increased risk of all-grade and severe-grade (3-5) eruptions associated with PI3K inhibitors.…”
mentioning
confidence: 53%
“…We defined rashes according to the Common Terminology Criteria for Adverse Events (CTCAE v 5.0). We appreciate Wu and colleagues' attention to detail and have added severe-grade rash data from the studies by Zelenetz et al study, Vuylsteke et al, and Bowles et al 1 In addition, we have corrected data for severe grade rash reported in the study by Powles et al 1 These corrections to the data on severe grade rash resulted in an increase to 17 trials comprising 4429 participants vs the originally reported 14 trials and 3750 participants; a change to no evidence of statistical heterogeneity (I 2 = 0%, Q = 7.16) from our previously reported significant statistical heterogeneity (I 2 = 43.62%, Q = 23.06); and a change in the pooled Peto odds ratio (OR) to 6.36 (95% CI, 4.58-8.83) and incidence of 3.41% from the originally reported pooled Peto OR of 4.64 (95% CI, 2.70-7.97) and incidence of 6.95%. In addition, we originally reported that subgroup analyses found an inconclusively higher incidence of severe rashes with the use of Pan-class compared with isoform-selective PI3K inhibitors; corrected subgroup analyses revealed that the incidence of severe rashes did not differ significantly between classes of PI3K inhibitors.…”
mentioning
confidence: 96%
See 3 more Smart Citations